Perbedaan Pengetahuan Pertolongan Pertama Dengan Metode Audio Visual Pada Siswa/I Kelas XI SMA Santo Thomas 1 Medan Tahun 2024 - Monica Gabriella Siahaan; Vina Yolanda Sigalingging; Helinida Saragih (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
Background: First aid is the initial action provided to an individual who experiences an injury or emergency condition before receiving further medical assistance. Adequate first aid knowledge is crucial in preventing further injuries and even death. According to WHO data (2018), accidents are the leading cause of injury and death among school-aged children. SMA Santo Thomas 1 Medan has a School Health Unit (UKS), yet many students still have limited knowledge of first aid. Therefore, this study aims to determine the effectiveness of the audiovisual method in improving students' first aid knowledge. Objective: This study aims to examine the difference in first aid knowledge levels before and after receiving health education using the audiovisual method among 11th-grade students at SMA Santo Thomas 1 Medan in 2024. Results: This research employed a quantitative descriptive method with a pre-post test design without a control group. The sample consisted of 81 randomly selected students. Before receiving health education, 93.8% of students had good knowledge, while 6.2% had sufficient knowledge. After the intervention using the audiovisual method, all students (100%) demonstrated good knowledge. Conclusion: The findings indicate that the audiovisual method is effective in enhancing students' first aid knowledge. Therefore, it is recommended to incorporate this method into school health education programs to improve students' preparedness in handling emergency situations.